Determinan Pencegahan Kecurangan (Fraud) dalam Pengelolaan Dana Desa - Renanda, Syadza Azalia; Robinson (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to examine the effect of variable suitability of compensation, internal control systems, morality, and competence of personnel for the prevention of fraud in village funds management. The study utilizes a questionnaire to collect data from 33 villages in Mukomuko Regency, with each village involving the head of financial staff, resulting in a total sample of 33 people. Data analysis is conducted using multiple linear regression. The result showed that the competence of personnel has a significant partial effect on fraud prevention in village funds management. However, suitability of compensation does not have a significant partial effect on the prevention of fraud in village funds management, internal control systems do not have a significant partial effect on the prevention of fraud in village funds management, and morality does not have a significant partial effect on prevention of fraud in village funds management. Nevertheless, the suitability of compensation, internal control systems, morality, and competence of personnel collectively have simultaneous effects on the prevention of fraud in village funds management. The magnitude of the effect was 61,9% while the rest (31,8%) was effected by other variables that were not studied in this research.